2017
DOI: 10.1097/olq.0000000000000649
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Home-Based Syphilis and Human Immunodeficiency Virus Testing Among Male Partners of Pregnant Women in Western Kenya

Abstract: Background Few men are tested for syphilis or HIV during their partner’s pregnancy, a high-risk period for HIV and syphilis transmission. Offering home-based rapid testing of syphilis to couples during pregnancy can support prevention efforts to reduce transmission of sexually transmitted diseases and adverse pregnancy outcomes. Methods We assessed men’s uptake of paired (separate tests, single blood draw) point-of-care syphilis and HIV tests within a randomized controlled trial of pregnant women who receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In addition, WHO advocates enhancing PHT as a key approach to enlarging HIV testing coverage [25,27]. Previous research provided some evidence on the use of HIVST kits among male partners distributed by pregnant women or female sex workers [28,37]; however, these findings could not be directly applied to MSM. Our study showed that provision of free HIVST kits could more than double the potential capacity for MSM to have PHT on average.…”
Section: Plos Medicinementioning
confidence: 99%
“…In addition, WHO advocates enhancing PHT as a key approach to enlarging HIV testing coverage [25,27]. Previous research provided some evidence on the use of HIVST kits among male partners distributed by pregnant women or female sex workers [28,37]; however, these findings could not be directly applied to MSM. Our study showed that provision of free HIVST kits could more than double the potential capacity for MSM to have PHT on average.…”
Section: Plos Medicinementioning
confidence: 99%
“…Cross-sectional study 188 male partners, Nyanza province Pregnant women and their male partners preferred home-based tests compared to clinic or VCT-center based (Mark et al, 2018) [26]…”
mentioning
confidence: 99%
“…32 Other options that have been successfully tried include home testing in Kenya and in Malawi. 33,34 In all our analyses, men who had a history of not seeking medical care due to cost had lower odds of PNC attendance, likely because they were concerned about medical costs associated with PNC attendance. Considering that paternal PNC attendance is free of cost at SUS hospitals in Brazil, this belief potentially reflects transportation costs or costs incurred by the visit, the cost of medications, and the loss of daily wage because of missed work.…”
Section: Discussionmentioning
confidence: 85%